Effect of Standardized Listening Skills Test on Students` Listening Comprehension and Self-Efficacy - Mustapha, Muhammad Ali; Abani, Fati Shettima; Lawan, Umar (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
The study examined effect of standardized listening skills test on students` listening comprehension and self-efficacy. A quasi-experiment design was used. The population of the study comprised all junior secondary school two (JSS II) students of a selected school in Maiduguri Metropolis, Borno State, Nigeria. Two intact classes of the same level from the selected school were targeted. Seventy (70) students were selected to participate in the study using purposive sampling technique. This technique was chosen due to easy-access to the participants and the nature of the study. A standardized test entitled ‘English Language Listening Skills Test’ (ELLST) was administered to determine the group`s homogeneity in the pretest and the effect of the treatment in posttest. The instrument was validated by experts in English language teaching and teachers of English in secondary schools. The reliability of the instrument was achieved through Cronbach Alpha's reliability index at 0.82, indicating a high level of reliability. Additionally, a self-efficacy scale adapted from existing validated instruments by Mills et al., 2006; Rahimi & Abedini (2009) was used to measure students’ beliefs in their listening abilities. The data were analysed using descriptive statistics and independent sample t-test. The treatment group received regular listening skills tests, while the control group did not. Results showed that the treatment group demonstrated significant improvements in self-efficacy, as measured by the Listening Self-Efficacy Scale. Furthermore, the treatment group outperformed the control group on a standardized listening comprehension test. The findings suggest that regular listening skills tests can enhance students' self-efficacy and listening comprehension. It is, therefore, recommended that schools and language programmes should include standardized listening assessments as a regular part of instruction to improve students’ comprehension skills and build test familiarity. Keywords: Standardized Listening Skills Test, Listening Comprehension, Vocabulary, Grammar, pronunciation & self-efficacy.